The Anti-Campylobacter Activity and Mechanisms of Pinocembrin Action - Klančnik, Anja (Microorganisms, 2019)
We investigated the anti-Campylobacter activity of pinocembrin and its mechanism of action, as well as Campylobacter responses to pinocembrin treatment at the genetic and phenotypic levels, using C. jejuni NCTC 11168 and a multidrug efflux system repressor mutant (11168ΔcmeR). At its minimal inhibitory concentration, pinocembrin significantly increased cell membrane permeability of Campylobacter. Interestingly, at sub-inhibitory concentrations, pinocembrin did not significantly alter membrane functionality and it increased bacterial fitness. Treatment with pinocembrin evoked decreased expression of ribosomal proteins and down-regulation of several NADH dehydrogenase I chain subunits and proteins involved in iron uptake. This suggests altered protein production and redox cycle and iron metabolism. Interestingly, the chelation of Fe ions during the treatment with pinocembrin increased C. jejuni survival, although there was no increase in the formation of reactive oxygen species. Pre-treatment of C. jejuni with sub-inhibitory concentrations of pinocembrin for 2 h resulted in a 1 log decrease in C. jejuni colony forming units in mice liver at 8 days post-infection, compared to untreated C. jejuni. These findings suggest that pinocembrin modulates the metabolic activity of C. jejuni and that pre-treatment of C. jejuni with pinocembrin influences its virulence potential in mice. This anti-Campylobacter potential of pinocembrin warrants further investigation.